Educational games: Enhancing learning through interactive experiences - Dogan, Yunus (Nova Science Publishers Inc., 2025)
In the ever-evolving landscape of education, the advent of digital technologies has catalyzed a profound transformation in how knowledge is imparted and absorbed. This book explores this dynamic shift, offering an in-depth examination of how digitization and gamification are reshaping educational practices across various disciplines. It delves into the concepts of digitization and digital transformation within education. As classrooms and curricula increasingly integrate digital tools, the roles of educators and learners are redefined, fostering new interactions and methodologies. Such topics include: the dual nature of digital gaming-its benefits and risks, the integration of digital games in second language acquisition (SLA), the potential of simulations as educational tools, the challenge of neuromyths-misconceptions about the brain that can misinform educational practices, and much more. Educational Games: Enhancing Learning Through Interactive Experiences is a comprehensive guide for educators, policymakers, and researchers interested in the intersection of education and digital technology. By synthesizing theoretical insights with practical applications, this book provides a roadmap for leveraging educational games to create more engaging, effective, and innovative learning environments. © 2025 by Nova Science Publishers, Inc. All rights reserved.